Highly Active TiO2 Microspheres Formation in the Presence of Ethylammonium Nitrate Ionic Liquid - Anna Gołąbiewska (Catalysts, 2018)
Spherical microparticles of TiO2 were synthesized by the ionic liquid-assisted solvothermal method at different reaction times (3, 6, 12, and 24 h). The properties of the prepared photocatalysts were investigated by means of UV-VIS diffuse-reflectance spectroscopy (DRS), Brunauer–Emmett–Teller (BET) surface area measurements, scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and X-ray photoelectron spectroscopy (XPS). The results indicated that the efficiency of the phenol degradation was related to the time of the solvothermal synthesis, as determined for the TiO2_EAN(1:1)_24h sample. The microparticles of TiO2_EAN(1:1)_3h that formed during only 3 h of the synthesis time revealed a really high photoactivity under visible irradiation (75%). This value increased to 80% and 82% after 12 h and 24 h, respectively. The photoactivity increase was accompanied by the increase of the specific surface area, thus the poresize as well as the ability to absorb UV-VIS irradiation. The high efficiency of the phenol degradation of the ionic liquid (IL)–TiO2 photocatalysts was ascribed to the interaction between the surface of the TiO2 and ionic liquid components (carbon and nitrogen).